Aplicação de modelos coesivos intrínsecos na simulação da propagação dinâmica de fraturas. - Amorim, José Adeildo de (2007)
The phenomena studied in Fracture Mechanics can be observed either in Nature, the most sophisticated systems or ordinary structures. As a consequence, Engineers need to be alert for investigating the variety of complex mechanisms, related with fracture processes, which are capable of appearing in these systems. The possibility of failure is a real premise has to be considered not only in the design of structures, but also throughout their life. Undoubtedly, in this context Fracture Mechanics should be used to carry out prognostics of potential crack propagation patterns, verifying if there exists or not risk of keeping a structure in service usage. An alternative formulation widely applied to simulate fracture behavior is the Cohesive Zone Modeling (CZM) approach. It is a scientific branch of Fracture Mechanics originally proposed by Barenblatt (1959, 1962) and Dugdale (1960), and which after Xu and Needleman s works (1993, 1994) has acquired a great acceptance in scientific community. For this reason, the present work employs Xu and Needleman s model to simulate dynamic crack propagation in brittle materials, introducing the Software for Simulation of Dynamic Cohesive Fracture (DyCOH), which is based on Object-Oriented Programming (OOP) paradigm for facilitating future reuse and extension of implemented code. Using DyCOH software two numerical applications are shown. First, for verification purpose, the classical Xu and Needleman s problem is simulated and the response of DyCOH is compared with literature results. Second, for didactic aspiration, a simpler problem is studied in order to understand the influence of loading speed on fracture patterns of a tie-bar.